Pengaruh Media Tanam Terhadap Perkecambahan Bibit Trambesi (Samanea aaman) - Herman Nomleni; Wilhelmina Seran; Astin E. Mau (Wana Lestari, 2024)
Trembesi (S. saman (Jacq.) Merr) is a fast-growing plant, very high CO₂ absorber, good groundwater absorber and able to reduce gas concentration effectively so that it can be used as a greening plant. This study aims to determine the influence of planting media on the germination of trambesi seedlings (Samanea saman) and to find out one of the planting media treatments that has the best influence on the germination of trambesi seedlings. This study was conducted with a Complete Random Design (RAL) with 5 treatments and each treatment was repeated 3 times with 15 experimental units. Each experiment requires 100 trambesi seeds, so that a total of 1,500 trambesi seeds are needed for the entire treatment and test. The results showed that the influence of planting media had a real effect on germination power, germination speed index and germination value and the effect of planting media on A1 treatment (50% soil + 50% rice husk charcoal) was the best treatment that affected germination power, germination speed index, and germination value. In this planting medium, plants can germinate well compared to other treatments.